2021
DOI: 10.1007/s00380-021-01861-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bioprosthetic valve type on peri-procedural myocardial injury and mortality after transcatheter aortic valve replacement

Abstract: Peri-procedural myocardial injury (PPMI) is a common complication after transcatheter valve replacement (TAVR), often remaining clinically silent. The role of valve type on PPMI and the association between PPMI and mortality are still unclear. We sought to evaluate predictors and outcome of PPMI after TAVR, and the impact of self-expandable valve (SEV) vs. balloon-expandable valve (BEV) deployment on PPMI. Consecutive patients who underwent successful TAVR in a single-center from January 2014 to December 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Previous studies have reported that renal dysfunction at baseline predicted a higher increase of myocardial injury after the procedure. Additionally, myocardial injury after TAVR could lead to conduction disturbances, which may contribute to the need for PPM implantation ( 14 16 ). Thus, lower average CrCl may lead to worse kidney function at baseline, which plays an important role in patients requiring PPM implantation after TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that renal dysfunction at baseline predicted a higher increase of myocardial injury after the procedure. Additionally, myocardial injury after TAVR could lead to conduction disturbances, which may contribute to the need for PPM implantation ( 14 16 ). Thus, lower average CrCl may lead to worse kidney function at baseline, which plays an important role in patients requiring PPM implantation after TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelialization process varies in time and completeness depending on the device size and type [13] and while theoretically, this may represent a concern for device thrombosis, currently there is no clear evidence that antithrombotic therapy has a true clinical impact [14]. On the other hand, it is well established that after TAVI patients are exposed to a higher and temporally variable risk of ischemic events, including transient ischemic attack (TIA), stroke, myocardial infarction (MI) [15][16][17][18][19][20][21][22][23][24] and valve thrombosis [25,26]. Hence, evaluating the impact of different antithrombotic strategies to mitigate this risk has been the core focus of multiple clinical studies.…”
Section: Rationale For Antithrombotic Therapy After Tavimentioning
confidence: 99%
“…The endothelialization process varies in time and completeness depending on the device size and type [13], and while, theoretically, this may represent a concern for device thrombosis, currently there is no clear evidence that antithrombotic therapy has a true clinical impact [14]. On the other hand, it is well established that after TAVI, patients are exposed to a higher and temporally variable risk of ischemic events, including transient ischemic attack (TIA), stroke, myocardial infarction (MI) [15][16][17][18][19][20][21][22][23][24], and valve thrombosis [25,26]. Hence, assessing the impact of various antithrombotic approaches and valve types [27] to minimize this risk has been the primary focus of numerous clinical studies.…”
Section: Rationale For Antithrombotic Therapy After Tavimentioning
confidence: 99%